Short waterlogging events differently affect morphology and photosynthesis of two cucumber (Cucumis sativus L.) cultivars - Olorunwa, Omolayo J.; Adhikari, Bikash; Brazel, Skyler; Popescu, Sorina C.; Popescu, George V.; Barickman, T. Casey (Frontiers in Plant Science, 2022)
Waterlogging induces growth and developmental changes in sensitive crops such as cucumber (Cucumis sativus L.) during early plant development. However, information on the physiological mechanisms underpinning the response of cucumber plants to waterlogging conditions is limited. Here, we investigated the effects of 10-day waterlogging stress on the morphology, photosynthesis, and chlorophyll fluorescence parameters in two cultivars of cucumber seedlings. Waterlogging stress hampered cultivars’ growth, biomass accumulation, and photosynthetic capacity. Both cultivars also developed adventitious roots (ARs) after 10 days of waterlogging (DOW). We observed differential responses in the light- and carbon-dependent reactions of photosynthesis, with an increase in light-dependent reactions. At the same time, carbon assimilation was considerably inhibited by waterlogging. Specifically, the CO2 assimilation rate (A) in leaves was significantly reduced and was caused by a corresponding decrease in stomatal conductance (gs). The downregulation of the maximum rate of Rubisco efficiency (Vcmax) and the maximum rate of photosynthetic electron transport (Jmax) were non-stomatal limiting factors contributing to A reduction. Exposure of cucumber to 10 DOW affected the PSII photochemistry by downregulating the PSII quantum yield (ΦPSII). The redox state of the primary quinone acceptor in the lake model (1-qL), a measure of the regulatory balance of the light reactions, became more oxidized after 10 DOW, indicating enhanced electron sink capacity despite a reduced A. Overall, the results suggest that waterlogging induces alterations in the photochemical apparatus efficiency of cucumber. Thus, developing cultivars that resist inhibition of PSII photochemistry while maintaining carbon metabolism is a potential approach for increasing crops’ tolerance to waterlogged environments.